Effects of Lysine deficiency and Lys‐Lys dipeptide on cellular apoptosis and amino acids metabolism. Issue 9 (20th July 2017) - Yin, Jie; Li, Yuying; Han, Hui; Zheng, Jie; Wang, Lijian; Ren, Wenkai; Chen, Shuai; Wu, Fei; Fang, Rejun; Huang, Xingguo; Li, Chunyong; Tan, Bie; et al.
Abstract : Lysine is a common limiting amino acid and there is a potential risk of lysine deficiency existing in developing countries, which may cause various physical problems, such as immune suppression, lower growth performance, cell arrest, and metabolic imbalance. The results show that lysine deficiency impairs amino acid metabolism and causes apoptosis in IPEC‐J2 cells and mice. Lys‐Lys dipeptide serves as a lysine source and alleviates lysine deficiency induced cellular imbalance and apoptosis. Abstract : Scope: Lysine (Lys) is a common limiting amino acids (AA) for humans and animals and plays an important role in cell proliferation and metabolism, while metabolism of Lys deficiency and its dipeptide is still obscure. Thus, this study mainly investigated the effects of Lys deficiency and Lys‐Lys dipeptide on apoptosis and AA metabolism in vitro and in vivo models. Methods and results: Lys deficiency induced cell‐cycle arrest and apoptosis and upregulated Lys transporters in vitro and in vivo. SLC7A11, a cystine‐glutamate antiporter, was markedly upregulated by Lys deficiency and then further mediated cystine uptake and glutamate release, which was negatively regulated by cystine and glutamate transporters. Meanwhile, Lys deprivation upregulated pept1 expression, which might improve Lys‐Lys dipeptide absorption to compensate for the reduced Lys availability. Lys‐Lys dipeptide alleviated Lys deficiency induced cell‐cycle arrest and apoptosis and influenced AA metabolism. Furthermore, the mammalian target of rapamycin signal might be involved in sensing cellular Lys starvation and Lys‐Lys dipeptide. Conclusions: Altogether, these studies suggest that Lys deficiency impairs AA metabolism and causes apoptosis. Lys‐Lys dipeptide serves as a Lys source and alleviates Lys deficiency induced cellular imbalance.